2011
DOI: 10.1039/c1dt11064k
|View full text |Cite
|
Sign up to set email alerts
|

A highly Lewis acidic triarylborane bearing peripheral o-carborane cages

Abstract: A triarylborane (2) bearing three o-carborane cages at peripheral positions on the aryl groups was prepared and its crystal structure was determined from X-ray diffraction study. Treatment of 2 with KF in the presence of 18-crown-6 led to the potassium salt, [2F](-). A UV-vis titration experiment carried out in THF/H(2)O (9/1 v/v) showed that 2 binds fluoride ions with a binding constant (K) of 4.8 × 10(4) M(-1), which is an order-of-magnitude greater than K for the mono-carborane substituted triarylborane. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 77 publications
3
45
1
Order By: Relevance
“…CV traces for the reduction waves of the disubstituted carboranes 3, 4 and 5 are depicted in Figure 4. These poorly resolved CV waves are typical for disubstituted carboranes as shown elsewhere 15,26 including diaryl-ortho-carboranes. 8,10-13 CV traces for the phenyl (3) and trimethylsilyl (5) derivatives show cathodic waves indicating a two-electron reduction and anodic waves corresponding to two one-electron oxidations after reduction.…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…CV traces for the reduction waves of the disubstituted carboranes 3, 4 and 5 are depicted in Figure 4. These poorly resolved CV waves are typical for disubstituted carboranes as shown elsewhere 15,26 including diaryl-ortho-carboranes. 8,10-13 CV traces for the phenyl (3) and trimethylsilyl (5) derivatives show cathodic waves indicating a two-electron reduction and anodic waves corresponding to two one-electron oxidations after reduction.…”
Section: Electrochemistrymentioning
confidence: 99%
“…All solvents were dried by standard methods and freshly distilled prior to use. The compounds 2-bromo-1,3-diethyl-1,3,2-benzodiazaborole, 17 2-bromo-1,3-diphenyl-1,3,2-benzodiazaborole (16), 19 4,5-dimethyl-N,N´-diphenylortho-phenylenediamine (25), 32 N,N´-dimesityl-ortho-phenylenediamine (26), 33 N,N´-di-tert-butyl-ortho-phenylenediamine(28), 34 1-tert-butyl-1,2-dicarbadodecaborane 35 and 1-trimethylsilyl-1,2-dicarbadodecaborane 35 were prepared as described in the literature. Compounds 22, 23, 29, 1,2-dicarbadodecaborane and 1-methyl-1,2-dicarbadodecaborane were purchased commercially.…”
Section: Generalmentioning
confidence: 99%
“…This result in turn indicates an additive effect of phosphine oxide groups on the Lewis acidity enhancement of the triarylborane. 11,16 Experimental General considerations All operations were performed under an inert nitrogen atmosphere using standard Schlenk and glove box techniques. 19 As shown in the DFT analysis, the observed LUMO stabilization of 1-3 could be mainly attributed to the inductive electron-withdrawing effect of the phosphine oxide groups.…”
Section: Electrochemical and Anion Binding Propertiesmentioning
confidence: 99%
“…To date, various concepts have been developed to enhance the Lewis acidity of the tri-coordinate boron atom. [15][16][17] In contrast to perfluorinated triarylboranes, these triarylboranes preferably possess ortho-protecting groups on the aryl ligand to endow the boron center with high stability while retaining high Lewis acidity. We have also demonstrated that the attachment of closo-1,2-C 2 B 10 H 12 , the so called o-carborane, at peripheral positions of triarylboranes greatly increases the Lewis acidity of the boron center (III).…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, many efforts have been devoted to enhance the Lewis acidity of triarylborane to overcome hydration of fluoride. Some of the plausible strategies are involved with the introduction of electron-withdrawing groups such as o-carborane cages [34,35] and cationic substituents [30,36e46] into triarylboranes or with the use of metal chelation [31,47], all of which were found to be effective in enhancing the Lewis acidity of a boron center. In particular, the cationic triarylboranes have been shown to increase largely the fluorophilicity of the boron center enough to be operating in aqueous media due to the favorable Coulombic attractions that assist BÀF dative interactions [38,39,41,43e45].…”
Section: Introductionmentioning
confidence: 99%